Myocardial Infarction its Etiology, Pathophysiology, Clinical Course and Treatment Methods - Akhrorov Abdulaziz Azizjonovich; Sobirova Dildora Ravshanovna (Scholars Digest Publishing, 2024)
This article discusses the causes, etiology, pathogenesis, clinical course of myocardial infarction, preventive measures to prevent the disease and methods of its treatment.
Keywords: Myocardial infarction, ECG, Acute period, moderate acute period, positive teeth, negative teeth.